O potencial de mercado de empresas atacadistas através do varejo de materiais de construção nos municípios paulistas, no segmento de materiais elétricos, entre 1997 e 2002 - Saheli, Sumaia (2006)
This paper is a study on the marketing potential of wholesale companies based on the retail of building supplies, in the São Paulo state municipalities, during the 1997 - 2002 timeperiods. The focus of this study is on the demand for power electrical supplies. The study comprehends: a literature review; the conduction of a field research together with building supplies retailers; the employment of several secondary data; and, an estimation of the market potential with the application of linear hierarchical models. The presented model has been developed in four steps. First, with the application of a three level hierarchical model, employment volume is estimated on the building supplies retailing for each municipality. This is based on the total wage and salary income of each municipality and, on the dynamism of the population in the microregions and the mesoregions of São Paulo state. Second, with a two level hierarchical model, retail sales revenue is estimated based on the employment volume generated by the retailing business. Third, based on a field research, a relationship between retail sales revenue and the market potential for the wholesale business is established. At last, the determined market potential is validated when compared to the annual sales of a wholesaler of reference. The verified results validate the application of the presented model. Either by means of direct or indirect data collection, the conducted research highlights the importance of the wholesale business, mainly as supplier for the retailing business, where this latter has increased with the stability of the economy. Thus, even in face of a tough environment competition, due to the strengthening of the retail business and the desire on the part of the manufacturers to expand direct sales, the wholesale business still retains its importance on the economy. Finally, it was observed that the spatial distribution of a determined market potential does not differ significantly from the distribution of the estimated employment density nor from the distribution of the estimated resale net revenue density of the retailer, which suggests that these variables may be used as proxies.